The Role of Vascular Cells in Pancreatic Beta-Cell Function - Burganova, Guzel; Bridges, Claire; Thorn, Peter; Landsman, Limor (Frontiers in Endocrinology, 2021)
Insulin-producing β-cells constitute the majority of the cells in the pancreatic islets. Dysfunction of these cells is a key factor in the loss of glucose regulation that characterizes type 2 diabetes. The regulation of many of the functions of β-cells relies on their close interaction with the intra-islet microvasculature, comprised of endothelial cells and pericytes. In addition to providing islet blood supply, cells of the islet vasculature directly regulate β-cell activity through the secretion of growth factors and other molecules. These factors come from capillary mural pericytes and endothelial cells, and have been shown to promote insulin gene expression, insulin secretion, and β-cell proliferation. This review focuses on the intimate crosstalk of the vascular cells and β-cells and its role in glucose homeostasis and diabetes.